2019
DOI: 10.1002/ab.21833
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relationship between moral disengagement and bullying roles in youth

Abstract: Over the last several years, researchers have become increasingly interested in the influence of moral factors on bullying behaviors. This is the first meta‐analytic review to exclusively examine the relationship between moral disengagement (MD) and the key bullying roles of bully, victim, defender, and bystander. Forty‐seven independent samples examining a total of 43,809 children/adolescents (aged 7–19) were included in this meta‐analysis. Results indicated a positive relationship between MD and bullying (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
132
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 83 publications
19
132
1
4
Order By: Relevance
“…Concurrent correlations between the two variables were also confirmed. In line with the social-cognitive theory on moral disengagement (Bandura, 2016) and prior cross-sectional studies (Killer et al, 2019), children who are more prone to moral disengagement tend to be more inclined to bully others. Also, children who more often bully others are more prone to develop a higher tendency of moral disengagement over time, independent of their initial levels of moral disengagement.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Concurrent correlations between the two variables were also confirmed. In line with the social-cognitive theory on moral disengagement (Bandura, 2016) and prior cross-sectional studies (Killer et al, 2019), children who are more prone to moral disengagement tend to be more inclined to bully others. Also, children who more often bully others are more prone to develop a higher tendency of moral disengagement over time, independent of their initial levels of moral disengagement.…”
Section: Discussionsupporting
confidence: 69%
“…Previous cross-sectional research has shown that moral disengagement is associated with bullying perpetration (Caravita, Gini, & Pozzoli, 2012;Fitzpatrick & Bussey, 2018;Gini, Pozzoli, & Hauser, 2011;Mazzone, Camodeca, & Salmivalli, 2016;Pozzoli, Gini, & Thornberg, 2016;Tanrikulu & Campbell, 2015;Thornberg & Jungert, 2014;Thornberg, Pozzoli, Gini, & Jungert, 2015; for a recent meta-analysis, see Killer, Bussey, Hawes, & Hunt, 2019). In the context of cyberbullying, a recent study found that moral disengagement was positively associated with revenge motive, harm motive, and dominance motive of perpetration (Tanrikulu & Erdur-Baker, 2019).…”
Section: Moral Disengagement and Bullying Perpetrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of moral disengagement mechanisms are moral justification (i.e., using worthy ends or moral purposes to excuse pernicious means), diffusion of responsibility (i.e., diluting personal responsibility because other people are also involved), disregarding or distorting the negative or harmful consequences of the actions, and blaming the victim (i.e., believing that the victim deserves his or her suffering). Moral disengagement is associated with greater aggression, including bullying (for a meta-analyses, see Gini et al 2014;Killer et al 2019), assisting and reinforcing (Gini 2006;Sjögren et al 2020;Thornberg and Jungert 2013), and less defending (Doramajian and Bukowski 2015;Gini 2006;Gini et al 2018b;Mazzone et al 2016;Obermann 2011;Pozzoli et al 2016;Jungert 2013, 2014;Thornberg et al 2015Thornberg et al , 2017; for a meta-analysis, see Killer et al 2019; for exceptions, see Barchia and Bussey 2011b;Sjögren et al 2020) in bullying and peer aggression among students.…”
Section: Moral Disengagementmentioning
confidence: 99%